2013
DOI: 10.17161/iallt.v43i1.8516
|View full text |Cite
|
Sign up to set email alerts
|

Online Peer Feedback in Beginners’ Writing Tasks

Abstract: This study contributes to the body of research that aims to understandthe relationship between online communication and foreign language(FL) learning, in particular when teachers seek to provide authenticopportunities for interaction for their learners. The study wasmotivated by efforts made in the New Zealand context to overcome thegeographic limitations of interaction between FL learners and nativespeakers. We report on the findings of an exploratory study into anonline reciprocal peer tutoring program estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Such interactions are often considered meaningful in language acquisition as they encouraged the use of vital language features to construct the CP. The findings of the current study are similar to Pinto-Llorente et al ( 2017), Tolosa et al (2013) and Vinagre and Muñoz (2011).…”
Section: Words In Context and Parts Of Speechsupporting
confidence: 93%
See 1 more Smart Citation
“…Such interactions are often considered meaningful in language acquisition as they encouraged the use of vital language features to construct the CP. The findings of the current study are similar to Pinto-Llorente et al ( 2017), Tolosa et al (2013) and Vinagre and Muñoz (2011).…”
Section: Words In Context and Parts Of Speechsupporting
confidence: 93%
“…Pinto-Llorente et al (2017) demonstrated that ODFs contributed to the development of grammar skills such as parts of speech, sentence types and vocabulary. Similarly, studies on language and writing development have investigated the success of the ODF platform in enhancing vocabulary, grammar and spelling (Tolosa et al, 2013;Vinagre & Muñoz, 2011). In the 21 st century, the ODF has become a relatively beneficial and prospective technical instrument, capable of attaining significant advancements in tertiary education through its potential to facilitate and alter education, as well as refine existing teaching and learning styles (Ahmadi, 2018) among instructors and learners (Sun & Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chen (2016) qualitative synthesis found that online peer feedback may not always produce positive results. Some research investigating the quality of online peer feedback has noted that peer feedback was generally related to lower-order concerns due to students' linguistic limitations (Schultz, 2000;Tolosa et al, 2013). Other studies found that peers lacked confidence and strategies when using online feedback (DiGiovanni & Nagaswami, 2001).…”
Section: Online Peer Feedbackmentioning
confidence: 99%
“…The findings are also consistent with those of Hsu (2019), which reveal that learners who are writing posts on wikis tend to focus more on grammar than on vocabulary. Similarly, Tolosa et al (2013) found that learners who are creating computer mediated feedback focus more on grammatical errors than on vocabulary errors. This explanation might explain why, in the present study, the grammatical accuracy of the experimental group improved over time.…”
Section: Discussionmentioning
confidence: 96%